Pembentukan Kontrol Diri melalui Dzikir Asmaul Husna Pada Siswa di SMA Negeri 1 Tarik Sidoarjo - Yuhro, Diana Rahmawati (Fakultas Dakwah UIN KHAS Jember, 2023)
It starts with the problem of students who often engage in behaviour that is not in accordance with school rules, such as skipping school, damaging school facilities, and other forms of mischief. From this problem, the teacher and students finally tried to implement a form of dhikr activity, namely Asmaul Husna, to hone the self-control of students at SMAN 1 Tarik Sidoarjo. It is hoped that activities carried out continuously will help students be more able to control themselves so as not to take actions outside the rules that apply at school. This research aims to find out how the dhikr of Asmaul Husna can shape self-control in students at SMA Negeri 1 Tarik Sidoarjo and what the results obtained after doing the dhikr of Asmaul Husna are on the formation of self-control in students at SMA Negeri 1 Tarik Sidoarjo. This research is qualitative research with a descriptive approach. The research subjects were determined using purposive sampling, namely students and teachers of BK SMAN 1 Tarik Sidoarjo. Data collection techniques include interviews, observation, and documentation. This research concluded that 1) The process of forming self-control in students at SMA Negeri 1 Tarik was carried out by the guidance and counselling teacher inviting students to read the Asmaul Husna together every time they wanted to start the learning process in class. This method is carried out routinely and continuously. The results of the Asmaul Khusna dhikr activity are that students are more disciplined, calmer, easier to remember lessons and more disciplined.